Respuesta :

Answer:

Step-by-step explanation:

Given:  ABCD is a parallelogram and BC=CQ.

To prove :  ar(ΔBCP)=ar(ΔDPQ)

Construction :  Join AC

Proof: ar(ΔBPC) = ar (ΔAPC) [Triangles on the same base and between same parallels]  .Similarly ,  

ar(ΔADC) = ar(ΔADQ).

Now, ar(ΔADC) = ar(ΔADP) +ar(ΔAPC)  and

ar(ΔADQ) = ar(ΔADP) + ar(ΔDPQ) (from figure)

We know, ar(ΔADC) = ar(ΔADQ) and ar(ΔADP) is common.

Therefore, ar(ΔAPC) = ar(ΔDPQ)

But , ar(ΔAPC) = ar(ΔBPC)

Thus, ar(ΔBPC) = ar(ΔDPQ)  

Hence proved.

Ver imagen boffeemadrid